Strategies for Cotton in West and Central Africa : Enhancing Competitiveness in the "Cotton 4" - Baghdadli, Ilhem (Washington, DC: World Bank, 2012)
The objective of this report is to identify ways of enhancing competitiveness through sector reforms in Benin, Burkina Faso, Chad, and Mali (the Cotton-4). The report promotes best practices to manage cost and define sales strategies so as to enhance the contribution of the cotton sector to shared growth and lessen the risk of contingent liabilities borne by the countries. Areas of improvement, investigated in the report, are associated with the following three targets: 1) increasing yields to produce larger volumes; 2) reducing cost and increasing the reliability of grading; and 3) enhancing sales revenues. The report also explains how these targets can be effectively pursued through sector reforms. Guidance is provided on the types of investors needed to improve the competitiveness of the cotton sector in West and Central Africa and ways to design privatization lots.